Myeloid/Lymphoid Neoplasms with ETV6::PDGFRB Fusion Gene: A Rare Case of Poor Response to Imatinib and Possible Transformation Mechanisms from Myeloid Neoplasms of Bone Marrow to T-Cell Lymphoblastic Lymphoma Invasion in Lymph Nodes - Gou Y; Tang Y; Liu S; Cheng S; Deng X; Wen Q; Feng Y; Peng X; Wang P; Zhang X (Dove Medical Press, 2023)
Yang Gou,* Yongjie Tang,* Shuiqing Liu, Siyu Cheng, Xiaojuan Deng, Qin Wen, Yimei Feng, Xiangui Peng, Ping Wang, Xi Zhang Medical Center of Hematology, Xinqiao Hospital of Army Medical University, Chongqing, People's Republic of China*These authors contributed equally to this workCorrespondence: Ping Wang, Medical Center of Hematology, The Xinqiao Hospital of Army Medical University, Chongqing, People's Republic of China, Email wpii_2002@sina.comAbstract: The ETV6::PDGFRB fusion gene is commonly reported in chronic myelomonocytic leukemia with eosinophilia, yet patients with ETV6::PDGFRB presenting myeloid and lymphoid neoplasms successively have not been reported. Here, we report the first case of a 35-year-old man with myeloid and lymphoid neoplasms harboring an ETV6::PDGFRB fusion gene who demonstrated poor response to imatinib. The patient was diagnosed with an ETV6::PDGFRB fusion gene myeloid neoplasm on initial diagnosis at our hospital. After 5 months of treatment with imatinib, he was diagnosed with T-cell lymphoblastic lymphoma. ETV6::PDGFRB turned negative after increasing the dose of imatinib, but enlarged superficial lymph nodes reappeared the following year. Notably, the patient exhibited a worse response to imatinib treatment. This study describes this rare case and speculates on a possible mechanism.Keywords: ETV6, PDGFRB, fusion, myeloid/lymphoid neoplasms, imatinib